A Swellable Microneedle Patch to Rapidly Extract Skin Interstitial Fluid for Timely Metabolic Analysis. Issue 37 (17th July 2017) - Chang, Hao; Zheng, Mengjia; Yu, Xiaojun; Than, Aung; Seeni, Razina Z.; Kang, Rongjie; Tian, Jingqi; Khanh, Duong Phan; Liu, Linbo; Chen, Peng; Xu, Chenjie
Abstract : Skin interstitial fluid (ISF) is an emerging source of biomarkers for disease diagnosis and prognosis. Microneedle (MN) patch has been identified as an ideal platform to extract ISF from the skin due to its pain‐free and easy‐to‐administrated properties. However, long sampling time is still a serious problem which impedes timely metabolic analysis. In this study, a swellable MN patch that can rapidly extract ISF is developed. The MN patch is made of methacrylated hyaluronic acid (MeHA) and further crosslinked through UV irradiation. Owing to the supreme water affinity of MeHA, this MN patch can extract sufficient ISF in a short time without the assistance of extra devices, which remarkably facilitates timely metabolic analysis. Due to covalent crosslinked network, the MN patch maintains the structure integrity in the swelling hydrated state without leaving residues in skin after usage. More importantly, the extracted ISF metabolites can be efficiently recovered from MN patch by centrifugation for the subsequent offline analysis of metabolites such as glucose and cholesterol. Given the recent trend of easy‐to‐use point‐of‐care devices for personal healthcare monitoring, this study opens a new avenue for the development of MN‐based microdevices for sampling ISF and minimally invasive metabolic detection. Abstract : A swellable microneedle (MN) patch is developed to rapidly extract skin interstitial fluid (ISF) for timely metabolic analysis. The MN patch can efficiently extract sufficient ISF in a few minutes and well maintain its structure. The ISF can be easily recovered by a centrifugation method for subsequent offline metabolic analysis.